(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Moskalyova L. Y. The training of future teachers with specialization «The Christian ethics». In the article the competence in the preparation of future teachers of Christian ethics, represented the essence of the main requirements for teachers, which should provide the educational process in this direction.